(untitled) (Anclajes, 2012)
As Inca Garcilaso de la Vega enters literacy —when translating León Hebreo’s Diálogos de amor—, the “fidelity” of the translator is attached not only to the linguistic ideology of Renaissance´s Humanism but also to juridical and religious restrictions. Considering this hypothesis, the following paper examines the translation strategies performed by the hybrid subjectivity built in Comentarios reales, carried out to strengthen the enunciator’s authority. The analysis of these strategies provides a solid ground to describe the complex “fidelity” of the mestizo, a translator always oscillating between the defiance of the law and tactical retreat.